Exploring demographic and lifestyle associations with patient experience following telephone triage by a primary care doctor or nurse: secondary analyses from a cluster randomised controlled trial. Issue 9 (18th May 2015) - Warren, Fiona C; Calitri, Raff; Fletcher, Emily; Varley, Anna; Holt, Tim A; Lattimer, Valerie; Richards, David; Richards, Suzanne; Salisbury, Chris; Taylor, Rod S; Campbell, John L
Abstract : Background: The ESTEEM trial was a cluster randomised controlled trial that compared two telephone triage management systems (general practitioner (GP) or a nurse supported by computer decision support software) with usual care, in response to a request for same-day consultation in general practice. Aim: To investigate associations between trial patients' demographic, health, and lifestyle characteristics, and their reported experiences of care. Setting: Recruitment of 20 990 patients occurred between May 2011 and December 2012 in 42 GP practices in England (13 GP triage, 15 nurse triage, 14 usual care). Method: Patients reported their experiences via a postal questionnaire issued 4 weeks after their initial request for a same-day consultation. Overall satisfaction, ease of accessing medical help/advice, and convenience of care were analysed using linear hierarchical modelling. Results: Questionnaires were returned by 12 132 patients (58%). Older patients reported increased overall satisfaction compared with patients aged 25–59 years, but patients aged 16–24 years reported lower satisfaction. Compared with white patients, patients from ethnic minorities reported lower satisfaction in all three arms, although to a lesser degree in the GP triage arm. Patients from ethnic minorities reported higher satisfaction in the GP triage than in usual care, whereas white patients reported higher satisfaction with usual care. Patients unable to take time away from work or who could only do so with difficulty reported lower satisfaction across all three trial arms. Conclusions: Patient characteristics, such as age, ethnicity and ability to attend their practice during work hours, were associated with their experiences of care following a same-day consultation request in general practice. Telephone triage did not increase satisfaction among patients who were unable to attend their practice during working hours. Trial registration number: ISCRTN20687662.